The investigation of the herpesviruses (BoHV-1 and BoHV-4) on the occurrence of the reproductive disorders in dairy cattle herds, Turkey - Bilge Dagalp, S.; Alkan, F.; Caliskan, E.; Yildirim, Y.; Oguzoglu, T. C.; Sahna, K. Can; Burgu, I. (Ecole Nationale Veterinaire Toulouse, 2012)
In this study, the effects of Bovine Herpesvirus 1 (BoHV-1) and Bovine Herpesvirus 4 (BoHV-4) on reproductive disorders such as postpartum and chronic metritis, abortus and repeat breeder were investigated serologically and virologically in dairy cows, classified as Group I (n=8 herds) and Group II (n=5 herds) according to the presence of the animals with and without reproductive disorders, respectively. For this purpose, a totally 1000 sera (781 from herds in Group I and 219 from herds in Group II) were tested for antibodies to BoHV-1 and BoHV-4 by commercial ELISA. Additionally vaginal discharge samples (n=65), tissue samples from aborted foetus (n=7) and leukocyte samples (n=119) from cattle in Group I and/or Group II were examined for BoHV-1 and BoHV-4 by Polymerase Chain Reaction (PCR). Data showed that the seropositivity rates were 52.3% and 47.9% for BoHV-1 in Group I and II, respectively. However, the rates were detected as 47.2% and 5.4% for BoHV-4 in Group I and II, respectively. Virological results are in concordance with serological results, which pointed the etiological role of BoHV-4 in reproductive disorders of Group I cattle alone or with some other agents such as BoHV-1.
Keywords: Bovine herpesvirus 1; bovine herpesvirus 4; reproductive disorders; antibody; polymerase chain reaction